Reduced muscle contractile function in elite young soccer players after a short-congested fixture period - Rojas-Valverde, D.; Gutierrez-Vargas, R.; Rudriguez-Montero, A.; Pereira, L. A.; Loturco, I.; Martin-Rodriguez, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Soccer is a very popular sport, which has been widely investigated. However, little is known about the effects of congested fixture periods on muscle mechanical responses since access to elite teams during competitive periods is highly restricted. Thus, the goal of this study was to describe the effects of a short-congested fixture period on the neuromechanical parameters related to fatigue and stiffness of elite young soccer players. Nineteen young elite male soccer players (age 17.13±0.51 years, body mass 69.00±1.22 kg, and height 174.09±0.84 cm) participated in the study. The players took part in a preparatory tournament for the FIFA® U-17 World Cup, composed of a total of six matches in 1 week. Pre- and post-tensiomyographic changes were assessed by means of the normalized response speed (Vrn) and other tensiomyographic markers related to muscle fatigue (i.e. maximum radial muscle displacement (Dm) and velocities of contraction at 10% and 90% (V10 and V90) of both legs in two muscles (biceps femoris and rectus femoris). The players presented a possible to likely impairment in Dm, V10, and V90 of both legs and muscles, with the exception of the non-dominant biceps femoris. Vrn did not vary in any condition, although it presented a slight tendency to decrease. The data demonstrated impairments in the tensiomyographic markers in both legs and muscles, with the exception of the non-dominant biceps femoris. A short-congested fixture period in young soccer players leads to a decrease in muscle stiffness due to cumulative fatigue and lack of muscle recovery, this despite the efforts made by the medical staff to counteract the fatigue caused by the games. The use of tensiomyographic markers could be advantageous for rapidly monitoring neuromechanical muscle impairments throughout competitive soccer periods.